2011
DOI: 10.1105/tpc.111.092163
|View full text |Cite
|
Sign up to set email alerts
|

MaizeRough Endosperm3Encodes an RNA Splicing Factor Required for Endosperm Cell Differentiation and Has a Nonautonomous Effect on Embryo Development    

Abstract: Endosperm and embryo development are coordinated via epigenetic regulation and signaling between these tissues. In maize (Zea mays), the endosperm-embryo signals are not known, but endosperm cellularization is a key event for embryos to form shoots and roots. We screened seed mutants for nonautonomous functions in endosperm and embryo development with genetically nonconcordant seeds and identified the recessive mutant rough endosperm3 (rgh3). The wild-type Rgh3 allele is required in the endosperm for embryos t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
88
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(93 citation statements)
references
References 87 publications
(96 reference statements)
2
88
0
3
Order By: Relevance
“…The RGH3 protein localizes to the nucleolus and to speckles in the nucleoplasm and colocalizes with U2AF 65 . The rgh3 mutant did not have a general splicing defect but affected AS of some transcripts and appeared to induce the use of noncanonical splice sites (Fouquet et al, 2011). SUPPRESSOR OF abi3-5 (SUA) is a novel SF in Arabidopsis that affects seed maturation by controlling AS of ABSCISIC ACID INSENSITIVE3 (ABI3).…”
Section: Function Of Sfs In Developmentmentioning
confidence: 99%
“…The RGH3 protein localizes to the nucleolus and to speckles in the nucleoplasm and colocalizes with U2AF 65 . The rgh3 mutant did not have a general splicing defect but affected AS of some transcripts and appeared to induce the use of noncanonical splice sites (Fouquet et al, 2011). SUPPRESSOR OF abi3-5 (SUA) is a novel SF in Arabidopsis that affects seed maturation by controlling AS of ABSCISIC ACID INSENSITIVE3 (ABI3).…”
Section: Function Of Sfs In Developmentmentioning
confidence: 99%
“…5E). Another U2AF splicing factor, ROUGH ENDOSPERM3, has been implicated in seed development (Fouquet et al, 2011), while GRMZM5G813627 may instead play a role in tassel.…”
Section: Seed Embryo and Endosperm Undergo Hundreds Of Developmentamentioning
confidence: 99%
“…Tissuespecific splicing patterns can also alter a transcript's sensitivity to regulation by microRNAs, such as the maize (Zea mays) SPX family, which produces miR827-sensitive isoforms that predominate in developing seedlings, while insensitive isoforms dominate other tissues (Thatcher et al, 2014). Gene expression changes in splicing factors also play key roles in guiding tissuespecific developmental processes, including seed development, where the U2AF splicing factor ROUGH ENDOSPERM3 has been shown to be involved in mediating the interaction between the embryo and endosperm (Fouquet et al, 2011). The control of these alternative splicing differences among different tissues is thought to be the result of differential splicing factor expression and is likely also influenced by tissue-specific methylation patterns (Regulski et al, 2013).…”
mentioning
confidence: 99%
“…Verification will come from genome-wide studies of AS in different organs and during development (Loraine et al, 2013) as has been shown in animals Kalsotra and Cooper, 2011;BarbosaMorais et al, 2012;Ellis et al, 2012). In addition, screens for mutants in various pathways have frequently identified splicing factors as modulators of functional proteins, indicating that these pathways are regulated via differential splicing (Lee et al, 2006;Monaghan et al, 2009;Sugliani et al, 2010;Fouquet et al, 2011;Koncz et al, 2012). There is an ever-growing body of literature on how alternative splicing (AS) influences important developmental and signaling pathways, and many important examples have been discussed in the accompanying review by Staiger and Brown (2013).…”
Section: Introductionmentioning
confidence: 99%